2012
DOI: 10.1042/bst20120033
|View full text |Cite
|
Sign up to set email alerts
|

Advances in TERS (tip-enhanced Raman scattering) for biochemical applications

Abstract: TERS (tip-enhanced Raman scattering) provides exceptional spatial resolution without any need for labelling and has become a versatile tool for biochemical analysis. Two examples will be highlighted here. On the one hand, TERS measurements on a single mitochondrion are discussed, monitoring the oxidation state of the central iron ion of cytochrome c, leading towards a single protein characterization scheme in a natural environment. On the other hand, a novel approach of single molecule analysis is discussed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
66
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 75 publications
(66 citation statements)
references
References 54 publications
0
66
0
Order By: Relevance
“…Due to the high spatial resolution, specificity, and sensitivity of TERS, analysis of DNA and RNA has attracted attention [89][90][91]. Any such analysis would invariably involve the investigation of the neat nucleobases adenine (A), cytosine(C), thymine (T), guanine (G), and uracil (U).…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…Due to the high spatial resolution, specificity, and sensitivity of TERS, analysis of DNA and RNA has attracted attention [89][90][91]. Any such analysis would invariably involve the investigation of the neat nucleobases adenine (A), cytosine(C), thymine (T), guanine (G), and uracil (U).…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…The simultaneous recording of both topographical and chemical information provided by TERS technique has, in very recent years, allowed a deeper insight into the surface properties of many systems at the nanoscale, 18,19 including bio-systems. [20][21][22][23][24][25][26] In particular, TERS analysis has been focused on the investigation of DNA-and RNA-based systems, 27-34 as well as proteins-related systems. 17,[35][36][37] Recently, notable progresses have been also achieved for more complex biosystems such as single amyloid fibril, 38 alginates, 39 insulin protofilaments, 40 virus, 41 hemozoin crystals, 42 as well as synthetic 43 or real cellular membranes.…”
mentioning
confidence: 99%
“…For example, the high spatial resolution of TERS allowed researchers to resolve individual nucleobases on both RNA and DNA strands. [46,47] It was demonstrated that all four nucleobases could be identified on both RNA and DNA strands. [48,49] Recently, Lipiec et al reported that, using TERS, molecular structure of terminal groups at DNA fragments can be probed, which consequently allowed the authors to identify double strand breaks of DNA.…”
Section: Applications Of Ters In Materials and Life Sciencesmentioning
confidence: 99%